2017
DOI: 10.1177/0844562117731975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simulation on Undergraduate Nursing Students’ Knowledge of Nursing Ethics Principles

Abstract: Background Undergraduate nursing education standards include acquisition of knowledge of ethics principles and the prevalence of health-care ethical dilemmas mandates that nursing students study ethics. However, little research has been published to support best practices for teaching/learning ethics principles. Purpose This study sought to determine if participation in an ethics consultation simulation increased nursing students' knowledge of nursing ethics principles compared to students who were taught ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
(9 reference statements)
0
5
0
1
Order By: Relevance
“…Fowler 15 found no evidence of stronger professional values in nursing students participating in a service-learning experience within a three-credit didactic BSN course compared to students who had not participated in the experience. In a study of BSN students at three universities, Donnelly et al 16 examined the effectiveness of a program that included an ethics consultation simulation as well as a didactic approach to teaching the ethical principles found in the first three Code provisions. While overall posttest scores increased significantly from pretest, students participating in the simulation did not have statistically significant higher scores than did those in the control group.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fowler 15 found no evidence of stronger professional values in nursing students participating in a service-learning experience within a three-credit didactic BSN course compared to students who had not participated in the experience. In a study of BSN students at three universities, Donnelly et al 16 examined the effectiveness of a program that included an ethics consultation simulation as well as a didactic approach to teaching the ethical principles found in the first three Code provisions. While overall posttest scores increased significantly from pretest, students participating in the simulation did not have statistically significant higher scores than did those in the control group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anecdotally, students reported feeling more prepared for real-world ethical dilemmas after participating in the simulation. 16 Posluszny and Hawley 13 compared the professional value scores of BSN nursing students: sophomores (who either had completed or were taking a course introducing professional values) and seniors (who had completed two professional value development courses). The authors reported no difference in total professional values scores between the new and graduating students, which indicated that the additional coursework did not appear to influence professional value development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Donnelly et al. ( 2017 ) conducted a simulation consisting of a 4‐week, 60‐min/week programme for sophomore and senior students. This quasi‐experimental study used a pre‐test/post‐test design with a randomized assignment of students from three universities into both control ( N = 66) and experimental ( N = 79) groups.…”
Section: Resultsmentioning
confidence: 99%
“…Simulation has been researched and evidence has demonstrated it has an influential impact on pre-licensure nursing education. [3][4][5][6] It has been an effective pedagogical teaching tool in a variety of nursing topics, such as knowledge and self-competence; [7] caring for victims of elder abuse and intimate partner violence; [8] nursing ethics principles; [9] end of life care attitudes [10] and caring for a patient with sickle cell anemia. [11] Educational opportunities that provide a variety of technological informatics skills, including simulation, are necessities in today's academic environment.…”
Section: Simulationmentioning
confidence: 99%